2012
DOI: 10.1016/j.jinf.2012.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent lung infections in patients with hematological malignancies and invasive pulmonary aspergillosis: How firm is the Aspergillus diagnosis?

Abstract: Summary Background Immunocompromised patients with hematological malignancies and/or recipients of hematopoietic stem cell transplants are constantly exposed to several fungal, bacterial, and viral respiratory pathogens. Methods We retrospectively evaluated all patients with invasive pulmonary aspergillosis (IPA) and underlying hematological malignancies for the presence of concurrent, microbiologically documented pulmonary infections during a 5-year period (2005–2010). Results We found 126 such patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 50 publications
0
23
0
Order By: Relevance
“…Scant data exist regarding MMPIs in immunosuppressed patients as the available literature consists of case reports, and small case series . In a large retrospective Swedish study, coinfection of mucormycosis and aspergillosis was reported at 6% in a subgroup of patients (n = 70) with haematological malignancies .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scant data exist regarding MMPIs in immunosuppressed patients as the available literature consists of case reports, and small case series . In a large retrospective Swedish study, coinfection of mucormycosis and aspergillosis was reported at 6% in a subgroup of patients (n = 70) with haematological malignancies .…”
Section: Discussionmentioning
confidence: 99%
“…are increasingly reported in such profoundly immunocompromised patients. Although the subject of isolated case reports and small case series, the occurrence of mixed mold pulmonary infections (MMPIs) has not been studied . Specifically, it is unclear patients with polyfungal pneumonia have more severe disease and worse outcome.…”
Section: Introductionmentioning
confidence: 99%
“…GM test is a method which adopts serum enzyme-linked immunosorbent assay to detect aspergillus galacto-glucomannan antigens, to confirm a diagnosis of aspergillosis (Godet et al, 2012;Reinwald et al, 2012;Stopiglia et al, 2012;Tabarsi et al, 2012). The sensitivity of GM test was 50-90% and the specificity was 80-90%, and usually demonstrating positive before the emergence of radiological evidence (Horbrecht et al, 2002;Georgiadou et al, 2012). The sensitivity of aspergillus fluorescence PCR for diagnosing aspergillus infection is high, but should pay attention to false positive that could be caused by confounding factors, eg., laboratory pollution.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, an important problem in the case of patients who are at high risk for IFIs is that these patients are frequently colonized or infected by multiple microbial species at the same time, a fact that can confound the results of diagnostic assays and often leads to wrong diagnostic assumptions that can adversely affect care. Indeed, in a recent retrospective study of hematologic malignancy patients, 53% of patients were diagnosed as having probable IA, and 29% of those with proven IA were coinfected with other bacterial species (249). A potential solution to this problem could be the use of a broad-range multiplex PCR that can detect a wide variety of both bacteria and fungi, known as the SeptiFast assay, which has been developed commercially and is being used as a method to identify the pathogen in cases of sepsis (250,251).…”
Section: Pcrmentioning
confidence: 99%